'Fixation' and 'the pivot': balancing persistence with flexibility in design and entrepreneurship. Issue 1 (3rd April 2018) - Crilly, Nathan
Abstract: 'Design fixation' occurs when exploration of the solution space is unintentionally constrained by designers' knowledge of prior solutions. The study of fixation is well established in design research but there has been little discussion of what might be learned about fixation from studying related phenomena in other creative practices. To address this, a series of interviews were conducted with technology entrepreneurs and the advisors who guide them. Analysis of the interview data was informed by concepts of creative fixation, cognitive entrenchment and psychological ownership, but also concepts of entrepreneurial pivoting, strategic change and business model innovation. The study shows that entrepreneurs must actively balance persistence with flexibility, a task that is influenced by (i) the entrepreneurs' commitment to their ideas, (ii) the expertise that they have developed, (iii) the information that they seek or are exposed to, (iv) the resources available to them, and (v) their orientation towards either the product or the market. Collectively, these findings can be applied to design research as proposals for new topics to study when investigating fixation. They also hold implications for design practice by suggesting what designers (and their managers) should reflect on when identifying opportunities to change design direction.